PENGARUH PERSEPSI RISIKO DAN PEMAHAMAN INVESTASI TERHADAP MINAT MAHASISWA BERINVESTASI (STUDI MAHASISWA MANAJEMEN KONSENTRASI KEUANGAN, FAKULTAS EKONOMI DAN BISNIS, UNIVERSITAS RIAU) - -, Gerry Tampubolon , Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study was to determine the effect of risk perception and understanding of investment on students' interest in investing. This research took place at the Faculty of Economics and Business, with a total of 80 respondents. In this study consists of four variables. These variables are Perceived Risk (X1), Understanding of Investment (X2), Student Interest in Investing (Y). The data analysis method uses the Quantitative Descriptive method with the Multiple Regression analysis tool, with the help of using a statistical application, namely SPSS version 23. The results of the study show that: 1) Perception of risk has a significant positive effect on students' interest in investing. 2) Understanding of Investment has a significant positive effect on Student Interests in Investing. Keywords: Risk Perception, Understanding of Investment,  Student Interests in Investing